Історія запровадження та функціонування гривні: від 1918 до 2008 року. (До 90-річчя закону про національну грошову одиницю – гривню) - Левченко, В. (Спеціальні історичні дисципліни: питання теорії та методики, 2009)
B 2008 г. наше государство отметило своеобразный юбилей – 90 лет назад Центральная Рада приняла Закон о денежной единице, чеканке монет и печати (изготовлении) государственных кредитных билетов. В статье автор описывает первые шаги формирования денежной системы в Украине и введения в оборот собственной денежной единицы – гривны, а также исследует юридические аспекты введения национальной валюты на современном этапе. In 2008 Ukraine celebrated a peculiar jubilee – 90 years ago the Tsentralna Rada passed the “Law on Monetary Unit, Coining Money and Printing State Banknotes”. The article describes the first steps related to formation of Ukraine’s monetary system and bringing the hryvnia, the national monetary unit, into circulation; it also sheds light on some legal aspects of implementing the national currency at the present stage.